THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES ON EMPLOYEE JOB SATISFACTION AT CLASS IIA KALIANDA - Umar, Abdullah; Pangestuti, Naniek (Universitas Nusa Cendana, 2025)
This study aims to analyze the impact of human resource management (HRM) practices on employee job satisfaction at Class IIA Kalianda Correctional Facility. The independent variable in this research is HRM practices, while the dependent variable is employee job satisfaction. This study employs a quantitative method with a survey approach. Data were collected through a questionnaire distributed to 85 employees using saturated sampling. The results of the data analysis using simple linear regression testing indicate that HRM practices have a significant effect on employee job satisfaction, with 36.2% of the variation in job satisfaction being influenced by HRM practices. Based on these findings, it can be concluded that good HRM practices significantly contribute to increasing job satisfaction. This study recommends enhancing training programs and offering more competitive compensation management to improve job satisfaction in correctional facilities. Keywords: Human Resource Management; Job Satisfaction; Correctional Facility; Compensation; Training; Performance Assessment